Analysis of effect of leadership and culture organization of work on discipline PT . Global Jaya Bangunan Pekanbaru - Ayu Andira; Sri Restuti; Restu ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted at PT Global Bangunan Jaya Pekanbarudoing business in Jalan Tuanku Tambusai 225 Pekanbaru . The purpose of this study is to examine and analyze whether leadership, and organizational culture and simultaneous partial effect on the discipline of employees at PT Global Bangunan Jaya Pekanbaru. The population in this study were all employees of PT. Global Bangunan Jaya Pekanbaru numbering as many as 57 people and all were sampled so that the sampling technique was conducted using census.Data analysis tool used is multiple linear regression , and hypothesistesting performed by t test, F test and the coefficient of determination (R2). Before testing the hypothesis , first testing the validity and reliability of the indicators of each variable and to test the assumptions of the classical linear regression model.Based on the results of research and discussion, it is known that the discipline of employees at PT Global Bangunan Jaya Pekanbaru has been good , as well as leadership, organizational culture and work environment provided bythe company, it is seen from respondents to each indicator variable. Significant effect of variable leadership, organizational culture and work environment for employee discipline PT Global Bangunan Jaya Pekanbaru, either partially or simultaneously . This is evident from the results of the t test and F test There is a strong positive relationship variables leadership, organizational culture and work environment with work discipline PT Global Bangunan Jaya Pekanbaru, is evident from the correlation coefficients. There is a high contribution of the variable leadership style , organizational culture and work environment of theemployee discipline PT Global Bangunan Jaya Pekanbaru, this is reflected in the coefficient of determination obtained.Keywords : Work Discipline , Leadership and Organizational Culture.